Multiethnic Regionalisms in Southeastern Europe Statehood Alternatives - Stjepanović, Dejan (Comparative Territorial Politics, 2018)
This book is based on a comparative study of regionalisms in Croatia's regions of Dalmatia and Istria as well as Serbia's Vojvodina. The monograph's main focus is on regionalist political party strategies since 1990, and within that, each case study considers history and historiography, inter-group relations, economics, and region-building. The analysis demonstrates that many of the common assumptions about the causal determinants of territorial autonomy projects and outcomes, as well as about a teleological and unidirectional path from regionalism to nationalism, do not stand up to scrutiny. The author introduces original concepts such as plurinational, multinational and sectional regionalism to theories of nationalism and territorial politics. This book will appeal to scholars and upper-level students interested in territorial politics, federalism, nationalism and comparative politics. .